2015
DOI: 10.1007/s10695-015-0143-9
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione and its related enzymes in the gonad of Nile Tilapia (Oreochromis niloticus)

Abstract: Glutathione (GSH) concentration, the activity of its metabolizing enzymes, glutathione transferase (GST), glutathione peroxidase (GPx), glutathione reductase (GR), and the antioxidant enzyme catalase (CAT) in O. niloticus ovary and testis were examined. GSH concentration of O. niloticus testis exhibited high concentration (129 ± 21 nmol/g tissue) compared with GSH concentration (49.2 ± 8.3 nmol/g tissue) in the ovary. GST, GPx, GR, and CAT activities of O. niloticus testis exhibited high values compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
1
3
1
Order By: Relevance
“…The seasonal investigations of both females and males GSI organized as the highest values were in spring, followed by summer, while the lowest female GSI values were in winter, and in autumn for males. Such results are in accordance with those of many studies (Njiru et al, 2006;Shalaby & Migeed, 2012;Hamed et al, 2016;Khallaf et al, 2020). This study also agrees with El-Kasheif et al (2013) and Khallaf et al (2020) concerning the fact that the female Nile tilapia individuals have higher value of GSI than males at constant age, length and season; besides, the seasonal variations of both O. niloticus sexes following nearly the same trend.…”
Section: Discussionsupporting
confidence: 93%
“…The seasonal investigations of both females and males GSI organized as the highest values were in spring, followed by summer, while the lowest female GSI values were in winter, and in autumn for males. Such results are in accordance with those of many studies (Njiru et al, 2006;Shalaby & Migeed, 2012;Hamed et al, 2016;Khallaf et al, 2020). This study also agrees with El-Kasheif et al (2013) and Khallaf et al (2020) concerning the fact that the female Nile tilapia individuals have higher value of GSI than males at constant age, length and season; besides, the seasonal variations of both O. niloticus sexes following nearly the same trend.…”
Section: Discussionsupporting
confidence: 93%
“…Unlike the hepatic tissue, the gonadal tissue showed alterations of the enzyme activity of the biotransformation system (GST) and the antioxidant system (SOD and GPx) after 14 days of exposure. These results are differently than expected, since the enzyme activities changes in this tissue are more difficult to detect than in the liver (Hamed et al, 2016). In this case, there was a reduction in GST and GPx activities at 25 µg.L -1 .…”
Section: Discussioncontrasting
confidence: 68%
“…This may be due to abundant GSH was crucial to the maturation of spermatozoa and its protection against oxidative stress. The suggested hypothesis also evidenced in an experiment on Oreochromis niloticus, showed that protection of sperm was con rmed by more GSH production in testis (Hamed et al 2016). Further, addition of 0.1mM melatonin signi cantly decreased H 2 O 2 (100 µM)-induced oxidative damage by the elevation in GSH content and activities of SOD, CAT and GPx in rabbit sperm (Zhu et al…”
Section: Discussionmentioning
confidence: 83%